Testing criminal career theories in British and American longitudinal studies - MacLeod, John (Elements in criminology, 2022)
"More recent research on age and crime has failed to unequivocally adjudicate these two positions, but it seems as if the "criminal career" camp has garnered more support. In other words, more recent research on age and crime has shown that there is a benefit to longitudinal methodologies, that something is to be gained by examining different parts of the criminal career, and that the relationship between age and crime is not entirely invariant"--